The effect of organizational climate on contextual performance with innovative work behavior as intervening variable (study on educational staff at private universities in Medan City) / Supriadi Ady Supriadi, Nadia Putri Mulia Nadia and Siti Ayuni Tri Anggita Anggita - Supriadi, Supriadi Ady; Nadia, Nadia Putri Mulia; Anggita, Siti Ayuni Tri Anggita (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
This research aims at identifying and analyzing the effect of organizational climate on the contextual performance of educational staff which is mediated by innovative work behavior both directly and indirectly. The hypothesis put forward in this study is that organizational climate has a positive and significant effect on the contextual performance of educational staff which is mediated by innovative work behavior both directly and indirectly.Based on analysis and evaluation of research data, it can be concluded that innovative work behavior has a positive and significant effect on performance of educational staff. Organizational climate has a positive and significant effect on performance of educational staff. Innovative work behavior and organizational climate have a positive and significant effect on performance of educational staff. Thus, proposed hypothesis is accepted.